AMELIORATIVE EFFECT OF RED ALGAE ACANTHOPHORA SPICIFERA AGAINST PUFFER FISH AROTHRON HISPIDUS INDUCED BIOCHEMICAL AND OXIDATIVE STRESS IN MICE. - K. MOHANA PRIYA,; SAMANTA S. KHORA,; SAMANTA S. KHORA, (International Journal of Pharma and Bio Sciences, 2013)
Acanthophora spicifera, red algae are known to possess antioxidant activities. The objective of this study is to evaluate the ameliorative effect of the ethyl acetate extract of A. spicifera against the puffer fish Arothron hispidus induced biochemical alterations and oxidative stress. 24 Mice were divided into four groups were used in this study. Group 1 received normal saline as control, Group 2 – 4 were administered with skin extract of puffer fish A. hispidus. Group 3, 4 were pretreated with the ethyl acetate extract of A. spicifera. Decreased level of AST, ALT, ALP, and Bilrubin were observed in the puffer fish extract administered group and it was significantly increased in drinking A. spicifera extract groups. A raise of TBARS and the decrease of antioxidant enzymes were observed in the skin extract treated group. TBARS and antioxidant enzymes SOD, Catalase levels were significantly restored in the group drinking the A. spicifera extract. Similarly it decreased the level of Cholestrol, Glucose, Protein, Creatinine, Urea The present study reveals the exposure of ethyl acetate extract of A. spicifera considerably reduced the effect of puffer fish A. hispidus induced toxicity in mice.